Puerperal women's perceptions regarding preparation for birth in prenatal care - Carla Andrea de Brito; Antonia Silvânete Saraiva Silva; Rachel de sá Barreto Luna Callou Cruz; Sarah de Lima Pinto (Universidade Federal do Ceará, 2015)
Objective: to understand the perception of puerperal women regarding preparation for birth in the prenatal period.Methods: qualitative and exploratory research, undertaken in a maternity unit with 30 puerperal women. The technique of semistructured interview was applied and the discourses were analyzed using the Discourse of the Collective Subject. Results: it was evidenced that the puerperal women perceive the preparation for birth as important for experiencing labor and childbirth. At the time of labor, the fear of the pain was the most frequent feeling. It was identified that preparation for the birth is limited to the passing on of information regarding signs and symptoms which indicate labor as they occur. Conclusion: the professional who assists the pregnant woman must have a broad view regarding her needs, indicating a need for continuing education.